Rat‐tail tendon fiber SAXS high‐order diffraction peaks recovered by a superbright laboratory source and a novel restoration algorithm. (15th May 2013) - De Caro, Liberato; Altamura, Davide; Sibillano, Teresa; Siliqi, Dritan; Filograsso, Giovanni; Bunk, Oliver; Giannini, Cinzia
<x xml:space="preserve">Abstract</x> The nanoscale structural order of air‐dried rat‐tail tendon is investigated using small‐angle X‐ray scattering (SAXS). SAXS fiber diffraction patterns were collected with a superbright laboratory microsource at XMI‐LAB [Altamura, Lassandro, Vittoria, De Caro, Siliqi, Ladisa & Giannini (2012). J. Appl. Cryst.45, 869–873] for increasing integration times (up to 10 h) and a novel algorithm was used to estimate and subtract background, and to deconvolve the beam‐divergence effects. Once the algorithm is applied, the peak visibility improves considerably and reciprocal space information up to the 22nd diffraction order is retrieved (q = 0.21 Å−1, d = 29 Å) for an 8–10 h integration time. The gain in the visibility is already significant for patterns collected for 0.5 h, at least on the more intense peaks. This demonstrates the viability of detecting structural changes on a molecular/nanoscale level in tissues with state‐of‐the‐art laboratory sources and also the technical feasibility to adopt SAXS fiber diffraction as a future potential clinical indicator for disease.